Instructional Strategy for Comprehensible Meaning-Focused Input: Backward Learning Instruction - Misnawati, Misnawati (Utamax : Journal of Ultimate Research and Trends in Education, 2023)
Backward Learning Instruction (BLI) is a recommended instructional practice to apply for an extensive reading and listening program to become comprehensible meaning-focused input as an initial idea from the flipped-learning model and backward design. This study explored how backward learning instruction as an instructional strategy applies in the learning process; and how students perceive backward learning instruction for comprehensible meaning-focused input. The author used a mixed method, with the descriptive and statistical description of 45 students from the law department at the Sekolah Tinggi Ilmu Hukum Pengayoman Bone, which was selected using purposive sampling. A study of the document was conducted to compile the BLI model, and a Guttman scale questionnaire was provided to gain firm and precise answers on BLI implementation. Then, the data were analyzed. The result presented the BLI model within three steps: 1) Preparing class, 2) Backward learning instruction, and 3) Knowledge enrichment. This study also found that BLI as an instructional strategy for comprehensible meaning-focused input showed a high agreement among students with high and very high categories converted by the students' propensity to respond to a scale. As an implication, BLI has contributed to providing solutions for learning the reading and listening comprehension process in distance, blended, and autonomous learning. EFL teachers, learners, and material developers must consider BLI as learning instruction due to its positive impact on students' self-faced learning.